Self Efficacy dengan Academic Dishonesty pada Mahasiswa Universitas Putra Indonesia “YPTK” Padang - Isna Asyri Syahrina (Jurnal RAP (Riset Aktual Psikologi Universitas Negeri Padang), 2016)
Abstrack: Self eficacy with academic dishonesty on students at the University Putra Indonesia "YPTK" Padang . This study aimed to examine the relationship between Self Eficacy with Academic Dishonesty on students at the University Putra Indonesia "YPTK" Padang. Type of this research was quantitative correlational. The population in this study amounted to 583 people. These samples included 145 people. The sampling technique in this study was stratified proportional random sampling. Measuring instruments used in the form of scale self eficacy and the scale of academic Dishonesty. Data analysis methods used to test the hypothesis is the product moment correlation (Pearson). The result showed the value of rxy= -0.287, p= 0.000 ( < 0.01).Keywords: Self eficacy, academic dishonesty, students. Abstrak: Self eficacy dengan academic dishonesty pada mahasiswa Universitas Putra Indonesia  “YPTK” Padang. Penelitian ini bertujuan untuk melihat hubungan antara Self Eficacy dengan Academic Dishonesty pada mahasiswa Universitas Putra Indonesia “YPTK” Padang. Jenis penelitian ini adalah kuantitatif korelasional. Populasi dalam penelitian ini berjumlah 583 orang. Sampel penelitian berjumlah 145 orang. Teknik pengambilan sampel pada penelitian ini adalah stratified proportional random sampling. Alat ukur yang digunakan berupa skala self eficacy dan skala academic dishonesty. Metode analisis data yang digunakan untuk pengujian hipotesis adalah korelasi product moment (Pearson). Hasil penelitian didapatkan rxy= -0,287 dengan nilai p = 0,000 (<0,01).Kata kunci: Self eficacy, academic dishonesty, mahasiswa.